Non-destructive chemical analysis of old South Arabian coins, fourth century BCE to third century CE - Kirfel, Armin; Kockelmann, Winfried; Yule, Paul (Archaeometry, 2011)
Studies on Old South Arabian (OSA) coinage are rare and state-of-the-art materials analysis for them lags far behind that of ancient Greece and Rome. Understandably, numismatists responsible for preserving their collections discourage destructive analyses. We have selected coins of the aesthetically and technically developed Himyarite Royal Raydan series (early first to late second century ce), so-called Old and New Style Athenian Imitations, among others to provide a wide spectrum of information on OSA coinage. We used non-destructive neutron diffraction to ascertain the metal compositions and corrosion products. Density determinations using gas-pycnometry support these experiments. The results provide detailed information with regard to a small, apparently homogeneous, selection of 10 Himyarite period specimens and first insights into the actual and the original metal compositions of about 90 coins of the three main OSA numismatic groups. The analytical results make clear which OSA coins originally were struck and which ones were cast. The analyses provide not only detailed information concerning the manufacture of the selected representative coins, but also suffice to cast a shadow on the reliability of commonplace macro-optical classification, which proves often to be inaccurate.